HUBUNGAN PENGETAHUAN DAN SIKAP PRIA LANSIA TENTANG ANDROPAUSE DI DESA LAMBANG SARI V KECAMATAN LIRIK - Sidri Rizqi Yuniati (Jurnal Kesehatan Husada Gemilang, 2019)
Andropause is a condition in which middle-aged men undergo the testosterone drops – that it is and the development of symptoms run gradually. The high risk of dropping hormones in andropause is more likely to cause psychological problems than physical problems. The purpose of the research was to discover the relationship between elderly-men’s knowledge about and attitude on andropause in Village of Lambang Sari V RW 002, Sub-district of Lirik in 2016. This research is the analytical quantitative with cross section observation in which elderly-men’s knowledge and attitude variables observed at once. The research was completed in RW 002, Village of Lambang Sari V, Lirik Sub-district on April 27-29, 2016. The sampling technique used in this research was total sampling technique, door to door method. The collected data was primary and secondary data, so they were analyzed thru the univariate and bivariate data analysis. The results prove that elderlymen’s knowledge about andropause in RW 002, Village of Lambang Sari V, Lirik sub-district is at good category (25 respondents or 62.5%), elderly-men’s attitude on andropause is at positive category (24 respondents or 60%). The decision is that there is relationship between good knowledge and positive attitude. It is suggested that the health workers advance the counselling about andropause over the banners and leaflets.